THE EFFECT OF BIOFERTILIZER FORMULATION TO PHYTOPLANKTON ABUDANCE AT PANGASIUS SP. POND IN THE PEAT SOIL - Abdul Halim Hanafi; Syafriadiman Syafriadiman; Niken Ayu Pamukas (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research has been conducted in December 2018 until January 2019 at Kualu Nenas village, Tambang, Kampar Riau and for the observation of phytoplankton conducted in environment quality Laboratory of Aquaculture, Faculty of Fisheries and Marine University Riau. The purpose of this research is to figure out the appropriate dose of biofertilizer formulations to increase the abundance of phytoplankton in a Patin fish pond. The method used in this research is the experimental method of using a complete randomized design of 1 factor, 5 levels of treatment and 4 times repeated. The use of a dose of biofertilizer formulation refers to Syafriadiman and Harahap (2017). The doses used in this study are: P0: Without biofertilizer formulations (control), P1: of biofertilizer formulations 700 g/m2, P2: biofertilizer formulations 750 g/m2, P3: biofertizer formulations 800 g/m2 and P4: biofertilizer formulations 850 g/m2. The results of this study showed the highest abundance of phytoplankton species recorded by the Chlorophyta class in P2, with an abundance of 27,867 cells/L and the highest total abundance also recorded by P2 is 48,943 cells/L.Keywords: phytoplankton, peat soil, biofertilizer formulation, Patin (Pangasius sp.)